2006
DOI: 10.1111/j.1365-2583.2006.00620.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of the pyrethroid resistance alleles of Vssc1 and CYP6D1 in house flies from the eastern United States

Abstract: House flies were collected from four dairies in Maine, New York, North Carolina, and Florida, where high levels of resistance to permethrin have been documented. Regions of two genes, CYP6D1 and Vssc1, having alleles that confer resistance to permethrin (and other pyrethroids) were analysed from individuals at each collection site. The combinations of resistance alleles for Vssc1 and CYP6D1 were highly variable between each state. The resistance allele CYP6D1v1 was found at a high frequency (0.63-0.91) at all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
92
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 49 publications
8
92
1
Order By: Relevance
“…In all cases, the PCR sequence was the sodium channel gene fragment. Interestingly, using the primers designed in our study, we did not detect any introns in this region in both house flies and German cockroaches as previously reported (Dong et al, 1998;Rinkevich et al, 2006). Except in the German cockroach ACY strain, different genotypes for the kdr locus were observed among individuals in the same population of each insect species.…”
Section: Kdr Allelic Variation At the Genomic Dna Levelsupporting
confidence: 56%
“…In all cases, the PCR sequence was the sodium channel gene fragment. Interestingly, using the primers designed in our study, we did not detect any introns in this region in both house flies and German cockroaches as previously reported (Dong et al, 1998;Rinkevich et al, 2006). Except in the German cockroach ACY strain, different genotypes for the kdr locus were observed among individuals in the same population of each insect species.…”
Section: Kdr Allelic Variation At the Genomic Dna Levelsupporting
confidence: 56%
“…Similarly, Rinkevich et al [10] reported that the resistance allele CYP6D1v1 was found at a high frequency (0.63 -0.91) in house fly populations at all sites. In the present study, the maximum frequency (0.8) of the kdr allele was found at Ajman.…”
Section: Discussionmentioning
confidence: 69%
“…Similarly, Huang et al [11] reported variabiliy in genotypes among house fly populations. Rinkevich et al [10] reported that combinations of pyrethroid insecticide resistance alleles of Vssc1 and CYP6D1 were highly variable between the states from which the house flies were collected. Resistant insects of the genotype kdr/kdr were detected at Abu Dhabi, Dubai, Fujairah, Ajman, and Ras Al-Khaymah.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The M918T mutation is not found in the absence of the L1014F mutation (Soderlund and Knipple, 2003) and it appears that the super-kdr allele evolved from the kdr allele (Rinkevich, 2005). There are two additional Vssc1-resistance alleles (L1014H), termed kdr-his1 and kdr-his2, found in the US (Liu and Pridgeon, 2002;Rinkevich et al, 2006). The kdr-his2 allele was found only in house flies collected from a NC dairy in 2002 (Rinkevich et al, 2006).…”
Section: Introductionmentioning
confidence: 98%